PENINGKATAN KETERAMPILAN MENULIS NARASI MENGGUNAKAN MEDIA AUDIO (TAPE RECORDER) di SEKOLAH DASAR - Suryanila, Siska (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This research is executed because student writing narration skill is low. This research aim to increase student writing narration skill. This research use to approach qualitative in the form of description about behavior to able to perceive, and quantitative approach in the form of reached result after study process. This research is conducted in two cycle that is cycle of I twice cycle and meeting of II counted once meeting. Student writing narration skill at cycle of I generally is still lower. At cycle of II student writing narration skill get better. Kata Kunci : keterampilan menulis narasi; media audio; sekolah dasar